Antibacterial Activity of Grepafloxacin - B Wiedemann; P Heisig (Canadian Journal of Infectious Diseases)
Grepafloxin has an extremely broad spectrum of activity. Its activity against Gram-positive bacteria exceeds that of currently available quinolones. Grepafloxacin-resistant mutants seem to occur less frequently than ciprofloxacin - or ofloxacin-resistant mutants, and the increase in minimum inhibitory concentration (MIC) against the former mutants is less than that of the latter. This applies only to the relative differences (in dilution steps); the absolute values are similar. Grepafloxacin kills Gram-positive bacteria at concentrations little above the MIC. Its pharmacodynamic profile against pneumococci is promising, favouring use of this drug for respiratory tract infections.